Smart nutrient management practices for sustainable crop production - Meena, B. P.; Yadav, D. K.; Shirale, A. O.; Rani, Khusbhoo; Behera, S. K.; Mohanty, M. (Indian Farming, 2025)
Global food security faces pressure from rising population, climate change, and shrinking natural resources. In India, the second-largest fertilizer consumer after China, fertilizers contribute 40–50% of yield gains, making nutrient management essential. Yet, inefficient use results in poor utilization efficiencies i.e. 30–50% for nitrogen, 15–20% for phosphorus, 50–80% for potassium, and <5% for micronutrients—leading to widespread deficiencies and declining nutrient use efficiency (NUE), especially in cereals like rice, wheat, and maize. To address this, Smart Nutrient Management (SNM) practices are vital. Based on the 4R nutrient Stewardship principle, SNM integrates Soil-Test Crop Response (STCR), Integrated Plant Nutrient Supply (IPNS), and Site-Specific Nutrient Management (SSNM). Tools like SPAD meters, leaf colour charts, and Green Seeker sensors guide in-season decisions, while organic residue recycling, microbial inputs, and crop residue management enhance soil health. Innovations like nano-fertilizers, green fertilizers, digital soil mapping, and IoT-enabled systems enable precision nutrient delivery. Together, SNM enhances productivity, improves NUE, lowers costs, and reduces environmental impacts.